Development of Interactive Learning Media for Fundamental Pencak Silat Techniques in Junior High School - Pradisetya, Bagus Yoga; Herman Dwi Surjono (International Journal of Technology and Education Research, 2026)
This study aims to develop, validate, and test the effectiveness of interactive learning media for fundamental Pencak Silat techniques for junior high school students. The background of this research is the difficulty students face in visualizing complex motor movements in Pencak Silat through conventional methods. This research employed the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study was conducted at SMP Muhammadiyah 4 Yogyakarta with 8th-grade students as the subjects. Data were collected using validation sheets from material and media experts, as well as student response questionnaires. The results showed that the developed media achieved a validation score of 83.9% from both material and media experts, placing it in the "Very Feasible" category. Furthermore, the media proved to be effective in improving student learning outcomes, evidenced by an average post-test score of 84.8% and an N-Gain score of 0.757, which is categorized as "High Effectiveness." This study concludes that the interactive learning media created with Adobe Flash CS6 is a viable and effective tool for enhancing the mastery of fundamental Pencak Silat techniques in physical education.